Strategi Mewujudkan Ekowisata di Subak Intaran Barat, di Kecamatan Denpasar Selatan, Kota Denpasar - WULANDARI, NI MADE MIA; WINDIA, I WAYAN; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.1, Januari 2020, 2020)
Strategies for Realizing Ecotourism in the Subak of West Intaran of South Denpasar Sub-District, Denpasar City Institutional development is a very important component in the success of agricultural development. Institutions that have an important role in agricultural development in Bali are the subak system. At the present day, Subak faces a serious challenge to maintain its existence. One of the concepts offered to overcome the problem of subak is through integrating agriculture with tourism. The synergy between agriculture and tourism is developed for example through various forms such as agrotourism and ecotourism. One subak that embraces the concept of ecotourism but still needs to be developed is the Subak of West Intaran. This study aims to determine the potential of Subak of West Intaran and the strategies to realize the ecotourism. Data collection was conducted through in-depth interviews and questionnaires through six key informants. Then the data were analyzed using the SWOT analysis method and IFAS & EFAS matrix analysis. The results showed that Subak of West Intaran did not fully meet the 6A ecotourism requirements and was in one quadrant with IFAS value of (1.56) and EFAS value of (0.72) which means that West Intaran Subak is strong and has a high chance of being developed into ecotourism. Recommendations that can be given to Subak of West Intaran, namely the government need to affirm regulations to forbid the selling of agricultural land, support for the preservation of subak must be given to all levels of society, and the establishment of an Ecotourism Management of West Intaran Subak.